An Analysis Of SAW, WP And TOPSIS Methods In Determining The Best Employees At The Department Of Horticulture And Plantation Crops Of Bengkulu Province - Tri Rizky Oktariany; Maryaningsih Maryaningsih; Aji Sudarsono (Jurnal Media Computer Science, 2022)
The Department of Horticulture and Plantation Crops of Bengkulu Province is one of the Government Agencies in Bengkulu Province, where the office has implemented Information Technology which is used to assist the data processing. Every The Department of Horticulture and Plantation Crops of Bengkulu Province conducts employee performance assessments. In accordance with Government Regulation of the Republic of Indonesia Number 30 of 2019 concerning Performance Assessment of Civil Servants Part Three Article 41 Point (2) The performance appraisal of civil servants as referred to in paragraph (1) can be carried out by giving each element of the assessment a weight of 70% for the SKP assessment and 30% for work behavior assessment or 60% for SKP assessment and 40% for work behavior assessment. At The Department of Horticulture and Plantation Crops of Bengkulu Province, it uses the weight of the PNS performance assessment with 60% for the assessment of SKP and 40% for the assessment of work behavior. In the process of managing the data, computerization has been used through the Microsoft Office application package. The application for determining the best employees based on employee performance appraisal data at The Department of Horticulture and Plantation Crops of Bengkulu Province was made to help facilitate the Department in determining the best employees through 3 (three) decision support system methods, namely the SAW, WP, and TOPSIS methods. Comparative analysis of the 3 methods SAW, WP and TOPSIS went through 3 stages, namely processing time, final assessment results and sensitivity tests carried out. Applications for determining the best employees based on employee performance appraisal data at The Department of Horticulture and Plantation Crops of Bengkulu Province were built using the Visual Basic .Net programming language and SQL Server 2008 database. Based on the black box testing that has been carried out, the results show that the functionality of the application for determining the best employees based on employee performance appraisal data at The Department of Horticulture and Plantation Crops of Bengkulu Province runs as expected and the application is able to display the results of comparative analysis of the SAW, WP and TOPSIS methods and is able to display sensitivity test results.